Biomarkers for adult-onset Still’s disease - V. Yu. Myachikova; O. Yu. Tkachenko; S. V. Lapin; E. S. Kuvardin; A. L. Maslyanskiy (Научно-практическая ревматология)
Adult-onset Still’s disease (AOSD) is a rare complex autoinflammatory disease of unknown etiology. The main problem, practitioners have been facing with when researching AOSD, is the lack of developed approaches to assessing the activity of the disease. Traditionally used standard markers of inflammation do not always reflect the real activity of AOSD, especially when a patient is already receiving anti-inflammatory therapy. The article presents original data on the study of biomarkers: interleukin-1 beta (IL-1b), interleukin-6 (IL-6), interleukin-18 (IL-18), ferritin, glycosylated ferritin, calprotectin, procalcitonin compared with C-reactive protein, leukocyte and neutrophil counts in patients with moderate and high activity of AOSD. The relationship between inflammatory biomarkers and the Pouchot systemic score was evaluated to identify promising laboratory indicators of disease activity.